Risk Factors Associated with the Consumption of Sugar-Sweetened Beverages among Czech Adults: The Kardiovize Study - Kunzova, Monika; Neto, Geraldo A Maranhao; Infante-Garcia, María M; Nieto-Martinez, Ramfis; González-Rivas, Juan P (Nutrients, 2022)
High consumption of sugar-sweetened beverages (SSBs) is associated with a higher risk of cardiovascular disease (CVD). The last report on the prevalence of SSBs consumption in Czechia was 17 years ago, an updated analysis will enable the design of appropriate public health policies. This study aimed to determine the prevalence of SSBs consumption in a Czech city during 2020 and 2022, and its association with cardiometabolic biomarkers, behavioral risk factors, and socioeconomic determinants. A total of 730 participants (33 to 73 years) were assessed from a random population-based survey. SSBs consumption was evaluated using two methods: by calorie amount, with a 24 h dietary recall, and by frequency, with a food frequency questionnaire. By calorie amount, the prevalence of SSBs consumption was none: 52.5%, low: 30.0%, and moderate−high: 17.5%; by frequency was never: 16.0%, occasionally: 64.1%, and daily: 19.9%. SSBs intake was higher in men (p < 0.001) and younger participants (p = 0.001). Men consuming daily had higher waist circumference and visceral fat area compared to both occasional and never consumers. Higher SSBs consumption was associated with low household income, middle education level, and high total energy intake. In total, 20% drank SSBs daily and 17.5% of participants consumed moderate−high calorie amounts of SSBs. These results represent an increase in the prevalence of SSBs consumption in the last two decades. Public health policies should target men of younger age and people with low education and income.
Keywords: Male; Risk Factors; epidemiology; soft drinks; Česká republika; Czechia; Adult; sugar-sweetened beverages; dospělí; mužské pohlaví; Sugar-Sweetened Beverages; Beverages; dieta; Czech Republic; lidé; Humans; cardiovascular disease; cukrem slazené nápoje; nápoje; rizikové faktory; Diet